Analysis of Activity Ratios and Profitability Ratios at PT PP London Sumatra Indonesia Tbk - Arlina Purba; Melinda Manik (Politeknik Negeri Medan, 2025)
This study aims to determine the level of activity ratio and profitability ratio at PT PP London Sumatra Indonesia Tbk during the period 2018 to 2024. The data collection technique uses documentation in the form of secondary data from the Statement of Financial Position and Income Statement obtained through the company's official website. Data is processed quantitatively using descriptive statistical analysis of the activity ratio and profitability. The results of the study indicate that the level of activity ratio experienced significant fluctuations in each period. A drastic decrease occurred in: receivables turnover in the 2024 period of 6.667 times, inventory turnover in the 2022 period of 7.024 times, working capital turnover in the 2024 period of 0.709 times, fixed asset turnover in the 2020 period of 0.560 times, and total asset turnover in the 2020 period of 0.324 times. Meanwhile, the highest increase occurred in: receivables turnover in the 2018 period of 26,442 times, inventory turnover in the 2021 period of 12,309 times, working capital turnover in the 2019 period of 2,144 times, fixed asset turnover in the 2024 period of 0.903 times and total asset turnover in the 2018 period of 0.400 times. The profitability ratio level also showed significant fluctuations each period. A significant decrease occurred in: the 2019 period, namely: return on assets of 2.471%, return on equity of 2.973%, gross profit margin of 15.180%, operating profit margin of 8.124%, and net profit margin of 6.829%. Meanwhile, the highest increases occurred in 2024, with a return on assets of 10.661%, a return on equity of 11.752%, a gross profit margin of 43.659%, an operating profit margin of 33.991%, and a net profit margin of 32.343%. Keywords: Financial Statements, Activity Ratios, Profitability Ratios